Birds of Costa Rica - Howell, Steve N. G.; Dyer, Dale (Artist) (Princeton, New Jersey : Princeton University Press, 2023)
"A state-of-the-art illustrated field guide to the birds of Costa Rica. Costa Rica is among the most popular birding destinations in the world, with a breathtaking diversity of neotropical birdlife and stunningly beautiful habitats ranging from shady mangrove swamps to mist-enshrouded mountaintops and verdant rainforests. Birds of Costa Rica is the essential illustrated pocket guide to this biologically rich country. It covers all regularly occurring bird species found in the region and features facing-page plates and text that make field identification easy. Concise species accounts describe everything from size and distribution to voice, habitat, and status. This compact guide also features progressive taxonomy and a wealth of color range maps. Covers more than 800 species of birds found in Costa Rica, includes more than 200 superb color plates, and features concise species accounts, facing-page plates and text, and up-to-date range maps. Its compact size and field-friendly layout make it the ideal travel companion for any birder"--
Frontmatter -- Contents -- Preface and Acknowledgments -- How to Use This Book -- Biogeography -- Taxonomy -- Species Accounts -- Part I -- Species accounts -- Part II -- Appendices -- References -- Index of English Names
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on June 13, 2023).
JSTOR
Keywords: Birds -- Costa Rica -- Identification; Oiseaux -- Costa Rica -- Identification; NATURE / Birdwatching Guides; TRAVEL / Central America; Birds; Costa Rica; Electronic books; Field guides